2021
DOI: 10.1177/00084174211034938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Therapeutic Powered Mobility Camp for Children with Severe Cerebral Palsy

Abstract: Background. Children and youth with severe cerebral palsy (CP) have limited independent mobility, which affects opportunities for overall development. Purpose. To examine the effectiveness of Power Fun, a therapeutic powered mobility summer camp. Methods. A quasi-experimental, repeated-measure design was used, with participants acting as their own control. Twenty-four participants with severe CP (aged 7–20 years) attended Power Fun for three weeks, five days/week. Assessments of powered mobility skills and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…The certainty of evidence about the positive effect of wheeled mobility interventions on basic mobility skills was the highest. A total of 13 studies reported data on the effectiveness of different interventions on basic mobility skills 36,39–43,46,48–53 . Rosenberg et al, 52 a study with high‐quality evidence and moderate risk of bias, reported on an intensive 3‐week power mobility camp, Power Fun 52 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The certainty of evidence about the positive effect of wheeled mobility interventions on basic mobility skills was the highest. A total of 13 studies reported data on the effectiveness of different interventions on basic mobility skills 36,39–43,46,48–53 . Rosenberg et al, 52 a study with high‐quality evidence and moderate risk of bias, reported on an intensive 3‐week power mobility camp, Power Fun 52 .…”
Section: Resultsmentioning
confidence: 99%
“…Developmentally appropriate games were adapted to the mobility levels of participants 52 . The results demonstrated significant improvements in children with different types of CP in basic mobility skills, in functional mobility skills in a structured environment, and functional mobility skills in an unstructured environment based on the 0 to 170 point scale of the Powered Mobility Program (PMP) 62 (∆ pre‐post = 52 points, p < 0.001) 52 . Comparable results on the PMP were seen in the feasibility study for the Power Fun wheelchair mobility camp where the PMP scores improved similarly (∆ pre‐post = 53 points, p = 0.043) 51 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations